Transition metal coordination complexes based on V-shaped bis-triazole ligand: syntheses, structures, and properties. Issue 7 (3rd April 2018) - Shi, Xiu Juan; Chen, Peng Yun; Wu, Ming Ze; Cai, Dong Chen; Tian, Li
Abstract: Hydrothermal reactions of 1, 3-bis(1, 2, 4-triazol-1-yl)benzene (btb) and M(NO3 )2 (M = Co 2+ (1 ), Cu 2+ (2 )) afforded two new coordination polymers, [Co(btb)2 (NO3 )(H2 O)]n ·NO3 ·H2 O (1 ) and [Cu(btb)2 (NO3 )2 ]n (2 ), respectively. Single-crystal X-ray diffraction reveals that1 crystallizes in the space group P21 /m and2 crystallizes in the space group Pī, both showing a double-stranded chain structure. The 1-D chains are interconnected via π ⋯ π interactions to lead to 2-D ladder-like supramolecular architectures. In addition, magnetic behavior and thermal stability of1 and2 have been investigated. For1, weak antiferromagnetic interactions are observed at low temperature, and the data obey the Curie–Weiss law χ M  = C/(T−θ), with C = 3.22 cm 3 ·mol −1 ·K and θ  = −10.39 K. For2, the decrease of the χ T vs. T curve at low temperature is the result of intermolecular antiferromagnetic magnetic interactions. Abstract :